Where Islam and Judaism Join Together - Har-El, Shai. author. aut Link
XVI, 226 p. 3 illus.
Keywords: Introducing a framework to generate new conversations about inter-religious dialogue and create a community of religions, Shai Har-El argues that Islam and Judaism, sister religions, are closely related to one another with roots intertwined in the land, in the language, and in the memories of shared history.